PENGARUH TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA DESA TERHADAP KINERJA PEMERINTAH DESA (STUDI PADA PEMERINTAH DESA KECAMATAN DAWUAN KABUPATEN SUBANG) - Rohaeni, Siti (Review of Accounting and Business, 2023)
This study, which examines the village government of Dawuan District, Subang Regency, attempts to ascertain the impact of accountability and transparency in village fund management on the functioning of village governments. This study employed a quantitative methodology that included a descriptive and verification approach. This approach makes use of primary data by sending out surveys. Ten villages in the Dawuan subdistrict made up the study's sample, and 47 persons participated as respondents. Purposive sampling is used in the sampling procedure. Analysis using multiple linear regression is the analytical technique employed. The study's findings demonstrate that village government performance is positively and significantly impacted by partial accountability and openness in village budget management. The functioning of the village government is positively and significantly impacted by the openness and accountability of the village fund management process.